2018
DOI: 10.3390/s18041075
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Detection and Characterization of Water-Ethanol Solution through Spiral-Coupled Passive Micro-Resonator Sensor

Abstract: We present a microfabricated spiral-coupled passive resonator sensor realized through integrated passive device (IPD) technology for the sensitive detection and characterization of water-ethanol solutions. In order to validate the performance of the proposed device, we explicitly measured and analyzed the radio frequency (RF) characteristics of various water-ethanol solution compositions. The measured results showed a drift in the resonance frequency from 1.16 GHz for deionized (DI) water to 1.68 GHz for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In order to overcome the limitations of the methods described above, recent research has focused on developing highly sensitive approaches for the in situ and real-time analysis of water content in organic solvents. Among the different approaches, electrical (e.g., capacitors, , resonators , ) and optical (e.g., fluorescent/colorimetric, ,, photonic/plasmonic , ) methods have been successfully reported. Among these, optical methods either exploit specific chemical reactions with water to enhances fluorescence and color changes or monitor refractive index changes ,, of the water–alcohol mixture using highly sensitive optical transducers, , with the advantages of higher sensitivity, lower detection limit, larger range, and improved portability with respect to electrical approaches.…”
mentioning
confidence: 99%
“…In order to overcome the limitations of the methods described above, recent research has focused on developing highly sensitive approaches for the in situ and real-time analysis of water content in organic solvents. Among the different approaches, electrical (e.g., capacitors, , resonators , ) and optical (e.g., fluorescent/colorimetric, ,, photonic/plasmonic , ) methods have been successfully reported. Among these, optical methods either exploit specific chemical reactions with water to enhances fluorescence and color changes or monitor refractive index changes ,, of the water–alcohol mixture using highly sensitive optical transducers, , with the advantages of higher sensitivity, lower detection limit, larger range, and improved portability with respect to electrical approaches.…”
mentioning
confidence: 99%
“…Except for dielectric properties measurement, it is also meaningful to realize the quantification of a given binary liquid mixture [ 38 , 39 ]. Taking the acetone/water mixtures as an example, Figure 16 plots the volume fraction of water as a function of resonance frequency.…”
Section: Fabrication and Measurementmentioning
confidence: 99%
“…Among them, resonant cavity method has become the main method to measure the dielectric constant of liquid for its high sensitivity, high precision, and low cost. The method of measuring the permittivity of liquid by microwave method can be divided into plane type [9,10], container type [11,12], and intrusive type [13,14]. In recent years, many studies on the measurement of liquid dielectric constant have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies on the measurement of liquid dielectric constant have been reported. A helical coupled passive resonator is proposed by Koirala et al [9], which uses a micropipette to drop the measured liquid onto the sensor surface. The planar liquid dielectric sensor needs to accurately control the volume of the liquid.…”
Section: Introductionmentioning
confidence: 99%